Characterization of a novel cysteine protease inhibitor in Baylisascaris schroederi migratory larvae and its role in regulating mice immune cell response - Xu, Jingyun; Gu, Xiaobin; Xie, Yue; He, Ran; Xu, Jing; Xiong, Lang; Peng, Xuerong; Yang, Guangyou (Frontiers in Immunology, 2022)
Baylisascaris schroederi (B. schroederi) is a severe threat to the survival of giant pandas. Currently, the immune regulation mechanism of B. schroederi is poorly understood. Cysteine protease inhibitors (CPI) play important roles in the regulation of host immune responses against certain nematodes. In this study, a recombinant CPI of B. schroederi migratory larvae (rBsCPI-1) was cloned and expressed, and the effects of rBsCPI-1 on the physiological activities and antigen presentation of monocyte-derived macrophages (MDMs) were analyzed. We also analyzed the regulatory effects of rBsCPI-1 on the proliferation and differentiation of CD4+ T cells. And further identified the signaling pathways which play important roles in this process. The results showed that rBsCPI-1 activated the TLR2/4-small Rho GTPases-PAK1 pathway. On the one hand, it increased the phagocytosis and migration of MDMs. On the other hand, it activated downstream MAPK and NF-κB signaling pathways to induce apoptosis of MDMs. rBsCPI-1 also induced MDMs to polarize to the M2 subtype, thereby exerting an immunosuppressive effect. Meanwhile, rBsCPI-1 inhibited the antigen presentation process by decreasing the expression of MHC-II molecules, further inhibiting the proliferation of CD4+ T cells and inducing a Th1/Th2 mixed immune response. Treg cells with immunosuppressive effects were increased. The PD-L2/PD-1 and CD80/CTLA-4 signaling pathways between MDMs and CD4+ T cells were also activated by rBsCPI-1. In conclusion, this study preliminarily confirmed that rBsCPI-1 affects the physiological activities and polarization of MDMs through the TLR2/4 signaling pathway, and further interferes with antigen presentation response, inducing CD4+ T cells to play an immunosuppressive cellular response during the migratory process of B. schroederi. Thus, this study will provide a reference for elucidating the immune evasion mechanism of B. schroederi and developing new drugs and protective vaccines against B. schroederi.